Application of electrochemical sensor containing VO-titania@MXene composite in detection of imidacloprid
By preparing VO-TiO2@MXene composite materials rich in oxygen vacancies and constructing electrochemical sensors, the problem of insufficient sensitivity and stability of imidacloprid detection in the prior art is solved, and efficient, fast and simple detection effects are achieved.
Patent Information
- Application Number
- CN202211215690.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-30
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2042-09-30
AI Technical Summary
In the prior art, the sensitivity and stability are insufficient when detecting imidacloprid, making it difficult to achieve fast, simple and efficient detection.
MXene of TiO2 intercalation (TiO2@MXene) was prepared by two-step pyrolysis method, and then electrochemical activation was performed to convert it into VO-TiO2@MXene rich in oxygen vacancies for construction of electrochemical sensors.
It realizes high sensitivity, rapid response and good stability detection to imidacloprid, low cost and simple process, and can be successfully used for imidacloprid detection and environmental monitoring.
Smart Images

Figure CN115656286B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrochemical sensors, and in particular to use of an electrochemical sensor containing a VO-TiO2@MXene composite material in detecting imidacloprid. Background Art
[0002] Imidacloprid is a highly effective neonicotinoid insecticide. As a systemic insecticide with significant insecticidal effects at low doses, it is widely used in the prevention and control of various crop pests. However, due to the excessive and inappropriate use of imidacloprid in agricultural activities, its residues will seriously threaten human health. Therefore, the development of a rapid, simple and sensitive imidacloprid detection method is of great significance for environmental monitoring. At present, the detection methods used for imidacloprid mainly include gas chromatography, high performance liquid chromatography, electrochemical methods and fluorescence polarization methods. Among them, the electrochemical method is a good strategy for the detection of imidacloprid due to its advantages such as simple operation, low cost, fast detection speed, high sensitivity and miniaturization. For electrochemical sensing analysis, the performance of the electrochemical sensor mainly depends on the characteristics of the constructed electrode interface. Therefore, exploring new electrode materials is crucial for the construction of high-performance imidacloprid sensing platforms.
[0003] As a new type of two-dimensional multilayer nanomaterial, MXene has been widely used in electrochemical sensing research in recent years due to its high specific surface area, excellent conductivity, unique layered structure and easy processing. For pure MXene, due to the high proportion of metal atoms on its surface, MXene is unstable in air (oxygen), and due to the van der Waals force between adjacent layers, the layered structure of MXene tends to restack, thus inhibiting its application in electrocatalysis. In recent years, it has been found that Ti 3 C 2 T x The edge Ti atoms on the MXene surface can serve as the catalyst for the generation of TiO 2 The effective nucleation sites can easily form TiO 2 Two-dimensional heterostructures intercalated with nanoparticles (TiO 2 @MXene). TiO 2 Nanoparticles grow uniformly between MXene layers and on the surface, which not only prevents the micro-stacking of MXene, but also improves the specific surface area, conductivity and stability of MXene. 3 C 2 T x Nanosheets as TiO 2 The supporting platform makes TiO 2 Evenly dispersed on Ti 3 C 2 T x On top, it prevents TiO 2 Self-aggregation of nanoparticles.
[0004] Oxygen vacancies (VO) are the most common defects in semiconductor materials, especially metal oxide semiconductors. Since they can effectively regulate the electronic structure of the catalyst surface, they have been widely used to improve the performance of electrocatalysts. Among them, oxygen vacancy defects on the surface of nanomaterials can greatly change their electronic structure and physicochemical properties, thereby promoting the adsorption of target substances during electrocatalysis. Recently, related literature has reported that TiO 2 The VO in the TiO2 is beneficial to form new active sites, improve electronic conductivity, and promote the redox reaction of the analyte. 2 @MXene system is expected to obtain a high-performance imidacloprid sensing detection platform. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides an electrochemical sensor containing VO-TiO2@MXene composite material for detecting imidacloprid. TiO2@MXene composite material is prepared by a two-step pyrolysis method. 2 Intercalated MXene (TiO 2 @MXene), and then the composite material was electrochemically activated to convert TiO 2 @MXene converted into VO-TiO rich in oxygen vacancies 2 @MXene. Based on VO-TiO 2 @MXene electrodes are directly used as an electrochemical sensing platform to determine imidacloprid. The detection method is simple to operate, has a fast response speed, high sensitivity, and good stability, making it possible to quickly detect imidacloprid on-site and online.
[0006] The present invention is achieved through the following technical solutions:
[0007] A first aspect of the present invention provides a VO-TiO 2 @The use of MXene composite electrochemical sensor in the detection of imidacloprid.
[0008] Preferably, the electrochemical sensor comprises a glassy carbon electrode, on which a two-dimensional heterostructure of VO-TiO 2 @MXene composites.
[0009] Preferably, the electrochemical sensor is prepared by the following method:
[0010] (1) Ti 3 C 2 T x The first calcination treatment was carried out in an air atmosphere, and then the calcined product was placed in a nitrogen atmosphere for a second calcination treatment, and TiO 2 @MXene;
[0011] (2) The TiO obtained in step (1) 2 @MXene is dispersed in N,N-dimethylformamide and ultrasonically dispersed to obtain TiO 2 @MXene suspension, and then TiO 2 @MXene suspension was drop-coated on the surface of a clean glassy carbon electrode, and after drying, a TiO 2 @MXene modified glassy carbon electrode;
[0012] (3) The TiO obtained in step (2) 2 The MXene-modified glassy carbon electrode was placed in a buffer solution with a pH value of 6.0 and treated by cyclic voltammetry to obtain VO-TiO 2 @MXene / GCE electrochemical sensor.
[0013] Preferably, in step (1), the temperature of the first calcination treatment is 200°C, and the heating rate is 5°C·min -1 , processing time is 1h.
[0014] Preferably, in step (1), the temperature of the second calcination treatment is 500°C, and the heating rate is 5°C·min -1 , the processing time is 2h.
[0015] Preferably, in step (2), the VO-TiO 2 The concentration of @MXene suspension is 2 mg mL -1 .
[0016] Preferably, in step (3), the buffer solution is sodium hydrogen phosphate / disodium hydrogen phosphate solution; the potential of the cyclic voltammetry is -2.0-2.0 V, and the number of treatment cycles is 10 cycles.
[0017] In a second aspect of the present invention, a method for detecting imidacloprid using the electrochemical sensor is provided, wherein:
[0018] A solution containing imidacloprid is added to the electrolyte solution, and the mixture is mixed to obtain a mixed test solution. After the electrochemical sensor is connected to the test circuit, the electrochemical sensor is immersed in the mixed test solution, and the reduction peak current value of the sensor is detected by linear scanning voltammetry. A standard curve is established with the concentration of imidacloprid and the reduction peak current value, and the concentration of imidacloprid in the test solution is calculated according to the standard curve.
[0019] Preferably, the potential range of the linear sweep voltammetry is -0.4 to -1.0V.
[0020] Preferably, the electrolyte solution is a 0.1 M phosphate buffer solution with a pH of 6.0.
[0021] Preferably, the detection range is 70 nM-70 μM, and the detection limit is 23.3 nM.
[0022] The beneficial effects of the present invention are:
[0023] 1. VO-TiO prepared by the present invention 2 The @MXene sensor exhibits excellent sensitivity, remarkable selectivity, reproducibility, and stability, which is directly attributed to its oxygen vacancy-modified 2D heterostructure with large specific surface area, high electronic conductivity, and fast electron transfer.
[0024] 2. The method for detecting imidacloprid of the present invention is simple to operate, has a fast response speed, high sensitivity and good stability, making it possible to quickly detect imidacloprid on-site and online.
[0025] 3. The electrochemical sensor prepared by the present invention has low cost, simple process and easy operation. It can not only be successfully used for the detection of imidacloprid, but also has high sensitivity (the detection limit of imidacloprid is 23.3 nM) and strong anti-interference (in the presence of Ca 2+ ,Mg 2+ , Cl - , NO 3 - , NO 2 - , simazine, parathion, acetylpyridin and thiocloprid, the current response of imidacloprid did not change significantly), good stability, etc. 2 @MXene material modified electrodes can be used to determine the imidacloprid content in the environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 For MXene (A) and TiO 2 @MXene(B) and VO-TiO 2 @SEM image of MXene(C);
[0027] Figure 2 TiO 2 @MXene / GCE (a), VO-TiO prepared in Example 1 2 @MXene / GCE (b) linear sweep voltammetric response to 10.0 μM imidacloprid;
[0028] Figure 3(A) is the linear sweep voltammetric response graph of the electrochemical sensor prepared in Example 1 for detecting different concentrations of imidacloprid; the curves are from bottom to top: linear sweep voltammetric response curves of imidacloprid solutions with detection concentrations of 70nM, 0.1μM, 0.3μM, 0.5μM, 0.7μM, 1.0μM, 3.0μM, 5.0μM, 7.0μM, 10.0μM, 20.0μM, 30.0μM, 40.0μM, 50.0μM, 60.0μM, and 70.0μM; (B) is the standard curve graph.
[0029] Figure 4 Under optimized conditions, 50 times the concentration of Ca 2+ ,Mg 2+ , Cl - , NO 3 - , interference of simazine, parathion, acetylpyridin and thiocloprid on the reduction peak current of 5.0 μM imidacloprid. DETAILED DESCRIPTION
[0030] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0031] As mentioned in the background technology, the layered structure of MXene tends to restack, which inhibits the electrocatalytic activity of MXene in electrocatalytic reactions. 2 –Ti 3 C 2 T X / CTAB / chitosan composite modified electrode for determination of nitrite by differential pulse voltammetry (Wang X, Li M, Yang S, et al. A novel electrochemical sensor based on TiO 2 –Ti 3 C 2 T X / CTAB / chitosan composite for the detection of nitrite[J].Electrochimica Acta,2020,359:136938.) The literature reports that in this electrochemical detection system, by using Ti 3 C 2 T x Preparation of TiO 2 @MXene, this material does not contain oxygen vacancies and can detect nitrite by oxidizing nitrite to nitrate, but cannot detect imidacloprid.
[0032] Based on this, the present invention provides an electrochemical sensor for rapid, efficient and sensitive detection of imidacloprid and its application. Firstly, a novel two-dimensional heterogeneous MXene (TiO 2 @MXene) composite material, and then the composite material is electrochemically activated to convert TiO 2 @MXene converted into VO-TiO rich in oxygen vacancies 2 @MXene. Based on VO-TiO 2 @MXene directly acts as an electrochemical sensor for the determination of imidacloprid in phosphate-supported electrolyte solution.
[0033] In this electrochemical detection system, by 3 C 2 T x In situ growth of TiO on MXene 2 Nanoparticles, successfully synthesized heterostructured TiO 2 @MXene. Multilayered MXene can effectively avoid TiO 2 The self-aggregation of nanoparticles, in addition, MXene with excellent electrical conductivity can accelerate the 2 The electron transfer of TiO2 was enhanced by a simple electrochemical activation strategy, which provided strong support for preventing structural changes during electrochemical processes. 2 MXene composites, utilizing TiO rich in oxygen vacancies 2 @MXene composite material reduces imidacloprid and realizes the detection of imidacloprid. Oxygen vacancies are vacancies formed when oxygen atoms (oxygen ions) in the crystal lattice are detached, resulting in oxygen deficiency. The formed oxygen vacancies are positively charged, so they can adsorb negatively charged functional groups or substances. 2 The oxygen vacancies in @MXene improve the selective adsorption of imidacloprid by the material. During the detection process, the detection object imidacloprid undergoes a reduction reaction to obtain a reduction peak current, thereby realizing the detection of imidacloprid. The composite material significantly improves the adsorption capacity of imidacloprid on the electrode surface, thereby greatly improving the detection performance of the imidacloprid sensor.
[0034] Compared with the TiO 2 –Ti 3 C 2 T X / CTAB / chitosan modified electrode for nitrite detection on MXene-derived TiO 2 Based on @MXene, the material was electrochemically treated by green and simple cyclic voltammetry to obtain TiO rich in oxygen vacancies. 2@MXene composites (VO-TiO 2 @MXene), the oxygen vacancies generated help to increase the rate of redox reactions on the electrode surface, thereby significantly improving the electrochemical activity of the composite material. At present, common methods for introducing oxygen vacancies into materials include heating hydrogenation, ion doping, high-energy particle bombardment, atmosphere deoxygenation, mechanochemical force and chemical reaction (Jing Liqiang, Yuan Fulong, Hou Haige, Xin Baifu, Cai Weimin, Fu Honggang. Relationship between surface oxygen vacancies of ZnO nanoparticles and their photoluminescence and photocatalytic properties [J]. Chinese Science (Section B Chemistry), 2004 (04): 310-314.). It is worth noting that these methods are difficult to achieve oxygen vacancies on semiconductors, which requires complex, strict or high-risk conditions, such as high temperature and hydrogen atmosphere. The present invention adopts a green and simple electrochemical treatment method to treat TiO 2 @MXene is treated, and a large number of active sites and reactive oxygen species generated during the electrochemical treatment not only promote the electron transfer on the electrode surface, but also significantly increase the adsorption of imidacloprid on the electrode surface, thereby greatly improving the detection performance of imidacloprid.
[0035] In order to enable those skilled in the art to more clearly understand the technical solution of the present application, the technical solution of the present application will be described in detail below in conjunction with specific examples. If the specific experimental conditions are not specified in the examples, they are usually in accordance with conventional conditions or the conditions recommended by the reagent company; the reagents, consumables, etc. used in the following examples, unless otherwise specified, can be obtained through commercial channels.
[0036] Example 1: Containing VO-TiO 2 Preparation of @MXene electrochemical sensors
[0037] 1. Ti 3 C 2 T x The first calcination treatment was carried out in an air atmosphere, and then the calcined product was subjected to a second calcination treatment in a nitrogen atmosphere, and TiO 2 @MXene;
[0038] 2. The TiO obtained in step (1) 2 @MXene is dispersed in N,N-dimethylformamide and ultrasonically dispersed to obtain TiO 2 @MXene suspension, and then TiO 2 @MXene suspension was drop-coated on the surface of a clean glassy carbon electrode, and after drying, a TiO 2 @MXene modified glassy carbon electrode;
[0039] 3. The TiO obtained in step (2) 2The MXene-modified glassy carbon electrode was placed in a buffer solution with a pH value of 6.0 and treated by cyclic voltammetry to obtain VO-TiO 2 @MXene / GCE electrochemical sensor, that is, an electrochemical sensor for rapid and efficient detection of imidacloprid.
[0040] TiO prepared in Example 1 2 @MXene scanning electron microscope (SEM) image Figure 1 As shown, the original MXene exhibits a layered accordion-like structure with a smooth surface ( Figure 1 A). In TiO 2 @MXene Figure 1 B), it still maintains the accordion layered structure, but the surface becomes very rough, and many nanoparticles grow evenly on the MXene nanosheets, indicating that TiO 2 @MXene has been successfully constructed. VO-TiO 2 @MXene SEM image ( Figure 1 C), TiO can still be observed 2 The nanoparticles are uniformly embedded in the MXene nanosheets. 2 @MXene and VO-TiO 2 There is no obvious difference in the morphology of @MXene, indicating that the electrochemical treatment has an important effect on the TiO 2 @MXene morphology did not change significantly.
[0041] Example 2
[0042] Detection of Imidacloprid Concentration
[0043] In a phosphate buffer (pH=7.0) containing different concentrations of imidacloprid (70 nM, 100 nM, 0.3 μM, 0.5 μM, 0.7 μM, 1.0 μM, 3.0 μM, 5.0 μM, 7.0 μM, 10.0 μM, 20.0 μM, 30.0 μM, 40.0 μM, 50.0 μM, 60.0 μM, 70.0 μM), the electrochemical sensor prepared in Example 1 was connected to a test circuit, and the imidacloprid concentration was measured by linear sweep voltammetry. The imidacloprid concentration was used as the abscissa (in μM) and the reduction peak current value was used as the ordinate (in μA). A standard curve I=2.414c+3.699 (R 2 =0.998, 70.0nM-10.0μM), I=0.4986c+22.51(R 2 =0.996, 10.0μM-70.0μM).
[0044] like Figure 3As shown, the modified electrode has a good linear relationship with imidacloprid, and has a wide linear range (70.0nM-70.0μM) and high sensitivity and a low detection limit (23.3nM), which fully demonstrates that the sensing electrode can successfully detect imidacloprid of unknown concentration.
[0045] Comparative example: TiO 2 @MXene / GCE
[0046] 1. Ti 3 C 2 T x The first calcination treatment was carried out in an air atmosphere, and then the calcined product was subjected to a second calcination treatment in a nitrogen atmosphere, and TiO 2 @MXene;
[0047] 2. The TiO obtained in step (1) 2 @MXene is dispersed in N,N-dimethylformamide and ultrasonically dispersed to obtain TiO 2 @MXene suspension, and then TiO 2 @MXene suspension was drop-coated on the surface of a clean glassy carbon electrode, and after drying, a TiO 2 @MXene modified glassy carbon electrode.
[0048] Test Example 1
[0049] The TiO prepared in the comparative example 2 @MXene / GCE, VO-TiO prepared in Example 1 2 @MXene / GCE sensor uses linear sweep voltammetry to detect imidacloprid and test the detection response of different modified electrodes to imidacloprid. The results are shown in Figure 2 .
[0050] Depend on Figure 2 It can be seen that the sensor prepared in Example 1 is different from the TiO 2 @MXene / GCE(a) can respond well to extremely low concentrations of imidacloprid, and its detection sensitivity is better than that of TiO 2 @MXene / GCE(b).
[0051] Test Example 2
[0052] The specificity of the electrochemical sensor prepared in Example 1 for detecting the concentration of imidacloprid was investigated: the change in the reduction peak current percentage of imidacloprid before and after the addition of interfering ions was investigated. The specific results are shown in Figure 4 ;Depend on Figure 4 It can be seen that when 50 times the concentration of Ca was added to the 5.0 μM imidacloprid solution, 2+ ,Mg2+ , Cl - , NO 3 - , NO 2 - , simazine, parathion, acetamiprid and thiacloprid, the reduction peak current percentage of imidacloprid did not change significantly (error range of ±5.0%), thus eliminating the interference of some common ions and pesticides.
[0053] Test Example 3
[0054] The accuracy of the electrochemical sensor prepared in Example 1 in detecting the concentration of imidacloprid was investigated: the standard addition method was used, apple juice and cabbage juice were used as samples, diluted 100 times with phosphate buffer solution (0.1M, pH 6.0), and then imidacloprid solutions of different concentrations were added. The above solutions were detected and analyzed using the sensor prepared in Example 1. The results are shown in Table 1.
[0055] Table 1
[0056]
[0057]
[0058] As can be seen from Table 1, the accuracy of the above detection is between 97.9% and 102.8%, and the relative standard deviation is between 2.69% and 4.33%, indicating that the sensor constructed by the present invention is feasible for the detection and analysis of actual imidacloprid samples.
[0059] In summary, the electrochemical sensor of the present invention can not only successfully detect imidacloprid, but also has the characteristics of high sensitivity, rapid detection, good stability, etc. The electrochemical sensor of the present invention can be used to determine the concentration of imidacloprid and the content of imidacloprid in apple cabbage; the preparation method of the electrochemical sensor of the present invention has low preparation cost, simple process and easy operation.
[0060] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. Application of an electrochemical sensor containing a VO-TiO2@MXene composite material in detecting imidacloprid, the electrochemical sensor comprising a glassy carbon electrode, the glassy carbon electrode being coated with a two-dimensional heterostructured VO-TiO2@MXene composite material; the electrochemical sensor is prepared by the following method: (1) Ti3C2Tx is subjected to a first calcination treatment in an air atmosphere, and then the calcined product is subjected to a second calcination treatment in a nitrogen atmosphere, and TiO2@MXene is obtained after cooling; (2) dispersing the TiO2@MXene obtained in step (1) in N,N-dimethylformamide, uniformly dispersing by ultrasonication to obtain a TiO2@MXene suspension, and then drop-coating the TiO2@MXene suspension on the surface of a clean glassy carbon electrode, and obtaining a glassy carbon electrode modified with TiO2@MXene after drying; (3) The TiO2@MXene modified glassy carbon electrode obtained in step (2) is placed in a buffer solution with a pH value of 6.0 and treated using cyclic voltammetry to obtain a VO-TiO2@MXene / GCE electrochemical sensor.
2. The use according to claim 1, characterized in that: In step (1), the temperature of the first calcination treatment is 200°C, and the heating rate is 5°C·min -1 , processing time is 1h.
3. The use according to claim 1, characterized in that: In step (1), the temperature of the second calcination treatment is 500°C, and the heating rate is 5°C·min -1 , the processing time is 2h.
4. The use according to claim 1, characterized in that: In step (2), the concentration of the TiO2@MXene suspension is 2 mg·mL -1 .
5. The use according to claim 1, characterized in that: In step (3), the buffer solution is sodium hydrogen phosphate / disodium hydrogen phosphate solution; the potential of the cyclic voltammetry is -2.0-2.0 V, and the number of treatment cycles is 10 cycles.